Performing Gameplay – A Study of Video Game Performance Workshops - Marleena Huuhka (Body, Space & Technology Journal, 2021)
This article examines performances produced in two Performing Gameplay workshops in 2017 and 2019. These performances are labeled as intermedial, as they were produced by using video games alongside live performers. The aim is to explore the changes frame of performance causes in players and games, as well as in performances, performers, and spectators. The article focuses on two main themes: the transformative process from gameplay to performance, and vice versa; and the significance of non-human participants in this process.